Prevalence and factors associated with obesity amongst employees of open-cast diamond mine in Namibia - Haufiku, Desderius; Amukugo, Hans Justus (International Journal of Advanced Nursing Studies, 2015)
The study investigated the prevalence and factors associated with obesity amongst employees of Pocket Beaches mine. Obesity rates are increasing at an alarming rate worldwide; 1.2 billion people worldwide are overweight of which 300 million are clinically obese. Of concern, is that obesity is a risk factor for many diseases, including hypertension, diabetes and other forms of cancers. Although there are several mine workers who on reporting to occupational health services for minor ailment are found to be overweight or obese, we are not certain about the extent with the problem. The health risk associated with obesity could cause a big loss to NAMDEB in terms of care cost, low productivity and absenteeism.The aim of this study was to investigate the prevalence and determinants of obesity amongst NAMDEB employees working at Pocket Beaches diamond mine.a descriptive; cross-sectional study measured the prevalence of obesity and describes the factors that are associated with obesity and overweight.Study population: NAMDEB employees who were working at Pocket Beaches mine. A simple random sampling technique was used to select participants. Eighty seven employees were selected from 188 total NAMDEB employees working at Pocket Beaches mine. Data was collected through interviews. Anthropometric measurements namely, weight, height and abdominal circumference were collected using a standard protocol.Data was analyzed using Epi Info 2002. Body Mass Index (BMI) was calculated as kg/m2. Overweight was defined as BMI = 25 to 29.9 kg/m2 and obesity as BMI ≥ 30 kg/m2. Waist Circumference ≥80 cm was used to identify central obesity in women and ≥90 cm in men. The frequency of participation in physical activity, barriers to physical activity and food consumption is reported in percent and means.The study found prevalence 42% overweight and 32% obesity among employees of NAMDEB. A significant number of participants 48% never participate in moderate exercise per week. 71% of participants reported lack of motivation exercising and too tired after work as the major barriers to physical activity. The consumption of fatty foods such as fried chicken and fried meat was common among study subjects. A large number of respondents 79% eat fried chicken regularly while 74% eat fried meat regularly. 79% of participants consumed inadequate fruits and vegetable (one fruit and vegetable per day). The two most mentioned reasons for low fruits and vegetables consumption were lacked of fruits and vegetables in hostel food menu, and 14% don’t like fruits.This study results revealed a high prevalence of overweight and obesity among employees. There is also low participation in physical activity and inadequate intake of fruits and vegetables among employees. Lack of motivation to exercise and unavailability of fruits and vegetable contributed to unhealthy lifestyles. Appropriate interventions are necessary in order to reduce the high obesity prevalence. Wellness program to promote physical activity should be introduced at Pocket Beaches mine. Management should engage Sodexho (catering company) to increase fruits and vegetables in the employees’ menu.